Facial protection and head injuries in ice hockey: a systematic review - Asplund, C.; Bettcher, S.; Borchers, J. (British Journal of Sports Medicine, 2009)
Objective: To summarise the best available evidence to determine if facial protection reduces head injury in ice hockey.